Város a megszállt országban : Kolozsvár az 1944-es német bevonulás után - Murádin, János Kristóf (Közép-Európai Közlemények, 2015)
This year there is the 70th anniversary of the German occupation of Hungary. Therefore with this study I would like to commemorate this very important historical event, which had decisive effects on the future of the Hungarian state and society as well. Naturally untill nowadays there had been appeared a lot of books, studies and scientific articles which presents the occupation, but most of them deals with the problem in general, referring to the whole country. In order to complete the general scene, in my study I focused only on the capital of the Northern Transylvanian region, reincorporated to the Hungarian Kingdom in 1940. The city of Kolozsvár (today officialy in Romanian language: Cluj-Napoca) was the administrative and cultural centre of the eastern part of Hungary in that time, therefore it shows very well the exact consequences of the occupation. First of all I shortly present the political and military conditions of the German invasion of the country, and after that the occupation process of Kolozsvár. For a better description of the entering of Wehrmacht troops in the city, I used some interviews made to persons who were eyewitnesses of the events. Beside these, I obtained a lot of dates from the local contemporary Hungarian and Romainan press, and several scientific volumes and articles published last years. The main objective of this study is to realize an analysis of the exact consequences of the German occupation of Kolozsvár in 1944 upon the population of the city, and especially upon the Jewish community. Through the description of the mass arrests of left wing sympathizers, and the collection of the Jews in ghettos, as well as the deportation process, I tried to present one of the most dramatic perriod of the old, historical city of Kolozsvár.